Optical Tomography System Using Charge-Coupled Device for Transparent Object Detection - Juliza Jamaludin; Wan Zakiah Wan Ismail; Irneza Ismail; Sharma Rao Balakrishnan; Rahim, RA; Rahiman, MHF; Wahab, YA; Rohani, JM; Sahrim, M (Univ Tun Hussein Onn Malaysia, 2024)
Indexed by WOS